The Effect Implementation of Pharmaceutical Service Standards on Increasing Patient Satisfaction at Puskesmas Sedinginan Kab. Rokan Hilir - Nurul Hidayati; Nuraini Nuraini; Ramadhani Syafitri Nasution (PROMOTOR, 2024)
The achievement of pharmaceutical services in Indonesia in 2022 reached 68.87%, exceeding the target of 60%, showing an increase from the previous year which was only 57.10% of the target of 55%. This research aims to see the effect of implementing pharmaceutical service standards on increasing patient satisfaction at the Sejiwan Rokan Hilir Community Health Center in 2023. The research method used was quantitative with a cross-sectional design. The results of the research show that reviewing prescriptions, drug information services, counseling, monitoring drug side effects, monitoring drug therapy, and evaluating drug use influence increasing patient satisfaction at the Sejiwan Rokan Hilir Community Health Center in 2023.